STRATEGIES FOR INTEGRATION OF INTERCULTURAL AWARENESS IN ENGLISH TEACHING - Hladkoskok, Lesia; Buhinska, Tetiana; Muradkhanian, Iryna (Видавничий дім «Гельветика», 2026)
In the contemporary globalized environment, where intensive intercultural contacts have become a habitual element of both professional and everyday interaction, effective intercultural communication is gaining the status of a key competence, particularly in the context of the growing role of the English language as a universal means of international communication. The changing sociocultural realities necessitate the development of not only linguistic skills among learners, but also the ability to interpret and adequately respond to culturally conditioned patterns of behavior, values, and communicative norms. In this regard, the study aims to provide a comprehensive analysis of current approaches to integrating intercultural communicative competence into English language teaching programs, to systematize effective methods, and to identify pedagogical conditions that promote the development of cultural sensitivity. The article explores the theoretical foundations of intercultural communication, traces the evolution of scholarly approaches to defining its structure and content, and substantiates the significance of this phenomenon for shaping a wellrounded linguistic personality capable of productive dialogue in multicultural communities. Considerable attention is devoted to the analysis of innovative methodological techniques aimed at enhancing cultural observation skills, empathy, and reflection. Among these are project-based technologies, intercultural case studies, simulation activities, and the use of authentic multimodal materials and digital platforms that model real communicative situations. The article also highlights the importance of critically examining stereotypes and cultural asymmetries, which often become sources of communicative barriers. The practical findings of the study demonstrate the need for the systematic integration of the intercultural component into curricula, for preparing teachers to work with cultural diversity, and for creating an educational environment that encourages open intercultural collaboration. The study concludes that English language teaching must shift from a linguocentric model to a communicative and cultural one, ensuring that students develop the readiness for effective interaction in a global society where cultural competence becomes no less important than linguistic proficiency.
Keywords: intercultural communication; English language; cross-cultural competence; literature; teaching methodology